2014
DOI: 10.6018/analesps.30.1.149411
|View full text |Cite
|
Sign up to set email alerts
|

Malestar psicológico y emoción expresada en cuidadores de pacientes con un trastorno de la conducta alimentaria

Abstract: Resumen: El objetivo principal del presente estudio fue evaluar el nivel de emoción expresada y de malestar psicológico en cuidadores de pacientes con un trastorno de la conducta alimentaria, considerando las diferencias en función de las características sociodemográficas y clínicas. Participaron 53 cuidadores de pacientes con un trastorno de la conducta alimentaria que estaban siendo atendidas en la unidad de trastornos alimentarios del hospital de San Juan, Alicante. El 39.6% de los cuidadores fueron hombres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 53 publications
0
1
0
Order By: Relevance
“…The results obtained showed that carers who participated in the programme improved their levels of well-being, reducing carer burden, psychological distress, and expressed emotion. In addition, only patients whose carers participated in the programme reduced their levels of anxiety, depression, and psychological distress while no change occurred in patients whose carers participated in the control group (Pérez-Pareja et al, 2014;Quiles Marcos et al, 2018). A recent review study analyzing the effectiveness of treatments for carers of ED patients concluded that ECHO also provides an intervention that can reduce service costs (Treasure et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…The results obtained showed that carers who participated in the programme improved their levels of well-being, reducing carer burden, psychological distress, and expressed emotion. In addition, only patients whose carers participated in the programme reduced their levels of anxiety, depression, and psychological distress while no change occurred in patients whose carers participated in the control group (Pérez-Pareja et al, 2014;Quiles Marcos et al, 2018). A recent review study analyzing the effectiveness of treatments for carers of ED patients concluded that ECHO also provides an intervention that can reduce service costs (Treasure et al, 2021).…”
Section: Introductionmentioning
confidence: 99%